Behavioral Nudging And Citizen Adoption Of E-Government Services: A Systematic Review Of Local Government Marketing Strategies - Wiwin Riski Windarsari; Hery Maulana Arif; Kong Chantha (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The increasing implementation of e-government services has transformed how local governments deliver public services and engage with citizens. However, despite significant investments in digital infrastructure, citizen adoption of digital government services remains inconsistent. This study systematically reviews the most effective marketing strategies for increasing citizen adoption of e-government services in local government contexts. Using a systematic literature review (SLR) approach based on PRISMA guidelines, this study synthesized evidence from 24 empirical studies retrieved through the Elicit academic search platform. The findings reveal that behavioral nudging is the most consistently effective strategy for promoting e-government adoption. Interventions involving simplification, default settings, social influence, facilitating conditions, and collective-benefit framing generated stronger adoption outcomes than passive mass-media campaigns and conventional promotional approaches. The review further indicates that trust, digital literacy, demographic characteristics, and service complexity significantly moderate the effectiveness of marketing interventions. In low-trust and digitally marginalized communities, community-based facilitation and peer mentoring approaches proved more effective than purely informational campaigns. Meanwhile, targeted digital communication and multichannel engagement strategies demonstrated positive outcomes among digitally literate populations. This study contributes to the e-government literature by integrating behavioral governance and public sector marketing perspectives into citizen adoption research. The findings suggest that successful digital governance depends not only on technological quality, but also on citizen-centered communication, trust-building mechanisms, and behavioral intervention strategies.